Elastic fibres are broadly distributed in tendon and highly localized around tenocytes. Issue 6 (15th April 2013) - Grant, Tyler M.; Thompson, Mark S.; Urban, Jill; Yu, Jing
Abstract Elastic fibres have the unique ability to withstand large deformations and are found in numerous tissues, but their organization and structure have not been well defined in tendon. The objective of this study was to characterize the organization of elastic fibres in tendon to understand their function. Immunohistochemistry was used to visualize elastic fibres in bovine flexor tendon with fibrillin‐1, fibrillin‐2 and elastin antibodies. Elastic fibres were broadly distributed throughout tendon, and highly localized longitudinally around groups of cells and transversely between collagen fascicles. The close interaction of elastic fibres and cells suggests that elastic fibres are part of the pericellular matrix and therefore affect the mechanical environment of tenocytes. Fibres present between fascicles are likely part of the endotenon sheath, which enhances sliding between adjacent collagen bundles. These results demonstrate that elastic fibres are highly localized in tendon and may play an important role in cellular function and contribute to the tissue mechanics of the endotenon sheath.